2018
DOI: 10.1523/jneurosci.0904-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric and Distant Effects of a Unilateral Lesion of the Primary Motor Cortex on the Bilateral Supplementary Motor Areas in Adult Macaque Monkeys

Abstract: A restricted lesion of the hand area in the primary motor cortex (M1) leads to a deficit of contralesional manual dexterity, followed by an incomplete functional recovery, accompanied by plastic changes in M1 itself and in other cortical areas on both hemispheres. Using the marker SMI-32 specific to pyramidal neurons in cortical layers III and V, we investigated the impact of a focal unilateral M1 lesion (hand representation) on the rostral part (F6) and caudal part (F3) of the supplementary motor area (SMA) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 59 publications
(106 reference statements)
6
24
0
Order By: Relevance
“…To assess the relationship between the number of BDA-labeled boutons with the interaction between motor impairment (PD symptoms based on manual dexterity in the modified-Brinkman board task post-ANCE transplantation (see above) and dopaminergic (tyrosine hydroxylase positive (TH+) neurons) loss in the substantia nigra pars compacta (SNpc), we performed a multivariable linear regression model test (MATLAB R2017b, function ''fitlm''; Contestabile et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…To assess the relationship between the number of BDA-labeled boutons with the interaction between motor impairment (PD symptoms based on manual dexterity in the modified-Brinkman board task post-ANCE transplantation (see above) and dopaminergic (tyrosine hydroxylase positive (TH+) neurons) loss in the substantia nigra pars compacta (SNpc), we performed a multivariable linear regression model test (MATLAB R2017b, function ''fitlm''; Contestabile et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…(Morecraft et al, 2016;Savidan et al, 2017) for the non-human primate). In a recent article from this laboratory, we reported that a unilateral lesion of the M1 hand area led to a variable interhemispheric asymmetry in the detection of layer V pyramidal neurons in SMA, identified with the marker SMI-32 (Contestabile et al, 2018). This anatomical variable interhemispheric Contestabile et al SMA in SCI monkeys 5 imbalance possibly reflects an adaptive interhemispheric contribution of the bilateral SMA to recovery, depending on the lesion size as well as on the duration of functional recovery (Contestabile et al, 2018).…”
Section: Introductionmentioning
confidence: 86%
“…In a recent article from this laboratory, we reported that a unilateral lesion of the M1 hand area led to a variable interhemispheric asymmetry in the detection of layer V pyramidal neurons in SMA, identified with the marker SMI-32 (Contestabile et al, 2018). This anatomical variable interhemispheric Contestabile et al SMA in SCI monkeys 5 imbalance possibly reflects an adaptive interhemispheric contribution of the bilateral SMA to recovery, depending on the lesion size as well as on the duration of functional recovery (Contestabile et al, 2018). It was argued that these observations may represent a putative anatomical support of diaschisis, originally defined as a "loss of function and electrical activity in an area of the brain due to a lesion in a remote area that is neuronally connected with it" (Finger, Koehler andJagella, 2004 andsee von Monakow, 1914).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The exact mechanisms behind this recovery are still a matter of debate. In this context, non‐human primate (NHP) models are valuable tools to study mechanisms of cortical plasticity following localized specific lesion of the motor cortex, such as interhemispheric changes of cellular density in premotor areas (Contestabile et al., ), in rewiring of cortico‐cortical connections (Dancause et al., ) or vicariation (Hoogewoud et al., ; Liu & Rouiller, ; Murata et al., ). Theories of functional recovery distinguished redundancy from vicariation (see Finger, for review; see also Slavin, Lawrence, & Stein, ).…”
Section: Introductionmentioning
confidence: 99%